Zooplankton in the Seagrass Beds of Nain Island - Tuliabu, Nelda; Rimper, Joice R.T.S.L; Warouw, Veibe; Kaligis, Erly Yosef; Rumampuk, Natalie Detty C; Ngangi, Edwin Leonardo Apolonio (Sam Ratulangi University, 2024)
This research was conducted in July 2022, the determination of sampling locations was carried out by purposive sampling, namely data collection with certain considerations to obtain samples that represent the research location area. Seawater samples were taken using a plankton net which was then used for the zooplankton identification process carried out in the Marine Biology Laboratory of the Faculty of Fisheries and Marine Science. Measurement of physical parameters of water chemistry consisting of temperature, salinity, and pH, was carried out in situ. The content of nitrate and phosphate was conducted at the WLN laboratory (Water Laboratory Nusantara-WLN). Zooplankton counts were expressed in ind/l. Qualitative determination of plankton was made up to the genus level. The results of zooplankton identification consisted of 5 genera namely Acartia, Cyclops, Euterpina, Nauplius, and Oithona. The calculation of zooplankton abundance is in the range of 3-5 ind/l. The highest abundance was found at station one which was 5 ind/l followed by station three which was 4 ind/l and then station two as much as 3 ind/l. The diversity index is in the range of 0.4740-0.7786, the uniformity index is in the range of 0.2945-0.7087, and the dominance index ranges from 0.5971-0.7744. Keywords: Zooplankton, Seagrass Meadow, Nain Island, Abundance, Biological Index. Abstrak Penelitian ini dilaksanakan pada bulan Juli 2022, penentuan lokasi pengambilan sampel dilakukan dengan cara purposive sampling yaitu pengumpulan data dengan pertimbangan tertentu untuk memperoleh sampel yang mewakili wilayah lokasi penelitian. Sampel air laut diambil dengan menggunakan plankton net yang selanjutnya digunakan untuk proses identifikasi zooplankton yang dilakukan di Laboratorium Biologi Kelautan Fakultas Perikanan dan Ilmu Kelautan. Pengukuran parameter fisik kimia air yang terdiri dari suhu, salinitas, pH, dilakukan secara in situ. Kadar nitrat dan fosfat dilakukan di laboratorium WLN (Laboratorium Air Nusantara-WLN). Jumlah Zooplankton dinyatakan dalam ind/l. Penentuan plankton secara kualitatif dilakukan sampai tingkat genus. Hasil identifikasi zooplankton terdiri dari 5 genus yaitu Acartia, Cyclops, Euterpina, Nauplius, dan Oithona. Perhitungan kelimpahan zooplankton berada pada kisaran 3-5 ind/l. Kelimpahan tertinggi terdapat pada stasiun satu sebesar 5 ind/l, disusul stasiun tiga sebesar 4 ind/l dan kemudian stasiun dua sebanyak 3 ind/l. Indeks keanekaragaman berada pada rentang 0,4740-0,7786, indeks keseragaman berada pada rentang 0,2945-0,7087, sedangkan indeks dominasi berkisar antara 0,5971-0,7744. Kata Kunci: Zooplankton, Padang Lamun, Pulau Nain, Kelimpahan, Indeks Biologi.